Climate protection versus convergence? - Yvan Lengwiler (University of Basel, Center of Business and Economics (WWZ), 2021)
Global economic convergence and protection of the climate are both worthwhile goals. Yet, there is an inherent tension between them. Greenhouse gases are a waste product that is often emitted in the production process. Limiting such emissions therefore hampers the accumulation of income and capital. I expand Solow's growth model to accommodate green house gases, and use this to estimate the contribution of such emissions to economic development. The sobering insight is that we would not have witnessed any convergence in the last 45 years if poorer countries had not increased greenhouse gas emissions.
Keywords: O44; 330; climate change; convergence; growth theory; growth accounting; green housegases; GHG; carbon emissions; pollution; poverty; natural resources